Local knowledge of the using tribe farmers in environmental conservation in Kemiren Village, Banyuwangi, Indonesia - Agus Prasetyo Utomo; Mimien Henie Irawati Al Muhdhar; Istamar Syamsuri; Sri Endah Indriwati (Biosfer: Jurnal Pendidikan Biologi, 2020)
Using Farmers (Banyuwangi ethnic community) in Kemiren Village uses their ancestral knowledge in utilizing natural resources and the environment so that its sustainability is maintained. This study aims to identify the local knowledge of Using farmers in Kemiren Village, Banyuwangi Indonesia which plays a role in preserving their natural resources and environment. The study uses a qualitative approach and the data collection using documentation, interview, and field observation techniques. Data analysis uses methods cross-referenced and repeated information. Local knowledge of Using farmers that used to manage the environment is in the form of values (togetherness, obedience, consensus, fairness and caring), norms (prohibitions/taboo and suggestions in utilizing natural resources), belief (providing labuhan/offerings and selamatan/ritual), and practices in utilizing natural resources. The primary key that plays a role in environmental preservation is a harmonious relationship among farmers.